Validation of Plagiochila fracta nomen nudum (Jungermanniopsida). East African bryophytes XXXI. - Pocs, Tamas (Phytotaxa, 2015)
The nomen nudum Plagiochila fracta Pócs was used for a species collected by Patricia Geissler during March of 1999 in Madagascar. The name was used in three publications, but was never properly and validly described. The aim of this paper is to provide a full description to this peculiar species, which seems to be endemic to the north-western region of Madagascar.